Static magnetic field assisted thawing improves cryopreservation of mouse whole ovaries - Liyuan Zhang; Mengqiao Chi; Yue Cheng; Zhongrong Chen; Yunxia Cao; Gang Zhao (Wiley, 2024)
Abstract Ovarian tissue cryopreservation is considered to be the only means to preserve fertility for prepubertal girls and women whose cancer treatment cannot be postponed. However, ovarian tissues are inevitably damaged by oxidative stress during cryopreservation, which threatens follicle survival and development, and thus affects female fertility. Therefore, reducing tissue oxidative stress injury is one of the major challenges to achieving efficient cryopreservation of ovarian tissues, especially for whole ovaries. Here, we proposed a new method to improve the antioxidant capacity of whole ovaries during cryopreservation, static magnetic field assisted thawing. The results demonstrated that the antioxidant capacity of the ovarian tissue was significantly improved by static magnetic field treatment. In addition, ovarian tissue allograft transplantation was carried out, which successfully achieved vascular regeneration and maintained follicular development. The findings of this study not only provide a new reference for the preservation of female fertility, but also is a major step forward in the cryopreservation of tissues and organs. It will have good application prospects in the field of assisted reproduction and cryo‐biomedicine.